UJI ANGKA KAPANG KHAMIR DAN IDENTIFIKASI Aspergillus species PADA JAMU KUNYIT DI DENPASAR SELATAN - I Nyoman Jirna (Jurusan Analisis Kesehatan, Poltekkes Kemenkes Denpasar, 2019)
ABSTRACTJamu kunyit is one of the traditional medicine that is believed to cure some diseases and very popular by the community. Jamu kunyit can be reduced in quality if there were mold, yeast, and the presence of Aspergillus sp. The purpose of this study is to determine the number of mold yeast, and identify Aspergillus sp. on jamu kunyit that sold in Denpasar Selatan. This study was descriptive by using cluster sampling technique. Jamu kunyit were cultured on SDA media, and the growing colonies were calculated to determine the value of the number mold and yeast. From the number a mold and yeast examination, there were 8 samples of jamu kunyit that exceeded standard (35%) and 15 samples of jamu kunyit in normal range (65%), 2 samples of jamu kunyit showed positive Aspergillus sp. and 21 samples of jamu kunyit negative Aspergillus sp. the type of Aspergillus found is Aspergillus niger. Many factors that can cause mold and yeast contamination are packaging, production, and storage.Keyword : Jamu kunyit, the number of mold yeast, Aspergillus sp.